Decision-making in environmental risk management: case study on adaptive strategies in U.S. cities under uncertainty - Sarah Ali Abdulkareem; Aws Hamid Mohammed; Shahd Nasser Saadi Hassan; Ahmed Mohammed Fahmi; Matai Nagi Saeed (Environment and Social Psychology, 2025)
Increasing pollution dynamics, resource availability uncertainties and climate variability pose great challenges to environmental risk management. Traditional regulatory systems are based on fixed policies that do not do well in dynamic environmental conditions. In this context, this study aims to assess adaptive environmental management strategies, combining real-time monitoring, predictive modeling and stakeholder engagement to enhance air and water quality and soil health. Based on a comparative exploration of static, adaptive and hybrid models, the results show that adaptive processes help lower pollutant concentrations, contribute to ecosystem resilience and help develop the public trust in environmental governance. According to the study, adaptive air quality management reduces PM2. 5 levels, and water quality improves as nitrate concentrations decrease by 38%. Adaptive interventions also lead to improvements in soil health, doubling organic matter and reducing pesticide residues by 18%. Moreover, adaptive governance models enhance stakeholder confidence in environmental policies by 30%, highlighting the need for transparency and flexibility in decision-making. This analysis was supported by regression modelling, Monte Carlo simulations, and ANOVA procedures, which provided robust validation of outcomes and quantified uncertainty across different intervention scenarios. These findings indicate that adaptive environmental governance constitutes a generalizable and resilient mechanism for mitigating ecological risk, to far greater effect than static regulatory ecosystems. In further studies, long-term sustainability, cost effectiveness, innovative methods of implementation such as AI-enabled environmental monitoring, could be examined that help facilitate policies. Adaptive strategies can facilitate sustainable environmental management and climate resiliency by connecting scientific data with policy decisions